Redesign Drainage Channel in Jetis District Mojokerto Regency - Nurhayati, Dyan Eka; Syafiarti, Arintha Indah Dwi (Journal of Civil Engineering, Planning and Design, 2024)
There are up to 50-centimeter-high puddles on the road due to the Jetis Road Drainage Channel in Mojokerto Regency's incapacity to handle the flood discharge from the drainage catchment area. The Jetis Road drainage channel's size and channel bed slope will be affected by the meeting point of the 1000 m long secondary channel and the Jetis Road drainage outlet. The objective of this research is to evaluate the efficiency of drainage channel design considering the implications of the drainage existing condition due to inconsistent dimension and sedimentation. The drainage channel is designed to handle a total discharge of 4.6 m3/sec during 10 years return of period. Under these circumstances, a trapezoidal channel with a width of one meter and a depth of two meters is needed. The Jetis Road drainage channel's enlarged dimensions result in a flood water level of 1.8. The Jetis Road drainage channel has a freeboard of 0.2 meters since the flood water level that occurs in the channel with its new dimensions is 1.8 meters. The flow rate in the intended channel serves as the control in this study to determine channel size. The channel's maximum flow velocity of 1.44 m/sec satisfies the 1.5 m/sec maximum flow velocity allowed in concrete channels.